1953
DOI: 10.1037/h0054392
|View full text |Cite
|
Sign up to set email alerts
|

Personality characteristics of accident repeating children.

Abstract: T HE accident proneness hypothesis simply stated is that there is a tendency for certain individuals to have repeated accidents. This was postulated to account for the early discovery that sample populations of adult workers included individuals who had more accidents than could be accounted for by chance alone. More recent findings appear to minimize the importance of the statistical evidence for the accident proneness hypothesis (3).If we are willing to accept Cobb's (3) assignment of the variance in acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

1966
1966
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Fuller (1948) found the highest injury rate among children reported to be 'insistent and obstinate'; those classified as 'rude' had higher injury rates than children regarded as 'courteous'. Krall (1953), on the basis of two 20 minute doll-play interviews with 32 'accident-prone' and 32 'accident-free' children ages 5-8 years, reported that the 'accident-prone' children revealed more aggression in doll-play and were quicker to express aggression than the 'accident-free' children. She also suggested that the accident repeaters were less readily oriented and demonstrated a higher activity level than the 'accident-free' children.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuller (1948) found the highest injury rate among children reported to be 'insistent and obstinate'; those classified as 'rude' had higher injury rates than children regarded as 'courteous'. Krall (1953), on the basis of two 20 minute doll-play interviews with 32 'accident-prone' and 32 'accident-free' children ages 5-8 years, reported that the 'accident-prone' children revealed more aggression in doll-play and were quicker to express aggression than the 'accident-free' children. She also suggested that the accident repeaters were less readily oriented and demonstrated a higher activity level than the 'accident-free' children.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…With respect to the personality maladjustment, Marcus, Wilson, Kraft, Swander, Southerland, and Schulhofer (1960) compared 23 high-accident children with 22 normally functioning children and found that those in the accident group were rated significantly lower during a psychiatric interview on a 'Total Adjustment Index'; Krall (1953) notes that her 'accident repeaters' were more often known to counselors than their 'accident-free' counterparts.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…By only including children with at least two accidents in the preceding 12 months, a group has been selected with a very high accident rate. Krall (1953), in a group of 5to 8-year-old children, defined her high accident group as those with three or more hospital -attended accidents in a 4-year period. A recent survey of 600 children in Nottingham showed that there was a group that had had 3 or more hospital-attended accidents in a 6-year period.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by the White House Conference of 1934 emphasized the significance ofthe home for personality development ofthe child and the damage resulting from the broken home. The broken home has been shown to be a factor in juvenile delinquency (Glueck and Glueck, 1950;Monahan, 1960), in schizophrenia (Pollack, Malzberg and Fuller, 1939;Hilgard and Newman, 1961), in depression in psychiatric patients (Beck, Sethi and Tuthill, 1963), in mental disturbance among children in lower socio-economic homes (Cobliner, 1963), in accident-proneness in children (Krall, 1953), and in adverse performance on intelligence and personality tests (Altus, 1958;Lcichty, 1960;Stephens, 1961;Maxwell, 1963). However, other studies have found no relationship between broken homes and the factors mentioned above (Burchinal, 1958;Myers and Roberts, 1959;Pitts et al, 1965).…”
mentioning
confidence: 99%